Outcomes of hippocampus-sparing lesionectomy for temporal lobe epilepsy and the significance of intraoperative hippocampography. Issue 3 (March 2021) - Yu, Hsiang-Yu; Lin, Chun-Fu; Chou, Chien-Chen; Lu, Yi-Jiun; Hsu, Sanford P.C.; Lee, Cheng-Chia; Chen, Chien
Highlights: Hippocampus-sparing lesionectomy can achieve excellent seizure outcomes in lesional TLE with a normal hippocampus on MRI. Complete resection of lesion is associated with good seizure outcomes. Spikes and high-frequency oscillations in the normal-looking hippocampus were common and not associated with poor seizure outcome. Abstract: Objectives: We investigated hippocampal-sparing lesionectomy (HSL) outcomes in temporal lobe epilepsy (TLE) and the significance of high-frequency oscillations (HFOs) detected by hippocampography in HSL. Methods: We retrospectively reviewed data from patients who underwent HSL for lesional TLE. Patients were included when MRI confirmed (i) a lesion limited to the temporal lobe with normal hippocampi preoperatively and (ii) hippocampal integrity postoperatively. Factors possibly related to outcomes were collected. Intraoperative hippocampography was reviewed, and spikes, ripples, and fast ripples were marked. Seizure outcomes were tracked ≥ 2 years. Postoperative neuropsychological tests were performed and analyzed. Results: We included 67 patients (35 males/32 females, median age at surgery 28 years, 57 seizure-free). Complete resection was significantly associated with being seizure-free without aura, an outcome achieved by 32 (69.6%) patients with complete resection vs 1 (12.5%) with incomplete resection ( p  = 0.004). Spikes/ripples/fast ripples appeared frequently in the hippocampus, occurring in 86.4%/82.4%/75.0% of cases before resection and 76.7%/78.1%/63.0% after resection. The presence and rate were unconnected to seizure outcome. Postoperative neuropsychological outcomes in intelligence and visual memory improved overall. Conclusions: HSL in lesional TLE can produce satisfactory seizure and cognitive outcomes. Intraoperative hippocampography-guided resection of apparently normal hippocampi should be performed cautiously and might not be necessary. Significance: This study provided evidence in decision making for patients with lesional TLE with a radiologically normal hippocampus.